Journeys to a Graveyard Perceptions of Europe in Classical Russian Travel Writing - Offord, Derek (International Archives of the History of Ideas Archives internationales d'histoire des idées, 2005)
Journeys to a Graveyard examines the descriptions provided by eight Russian writers of journeys made to western European countries between 1697 and 1880. The descriptions reveal the mentality and preoccupations of the Russian social and intellectual elites during this period. The travellers' perceptions of western European countries are treated here as an ambivalent response to a civilization with which Russia was belatedly coming into close contact as a result of the imperial ambition of the Russian state and the westernization of the Russian elites. The travellers perceived the most advanced European countries as superior to Russia in terms of material achievement and the maturity and refinement of their cultures, but they also promoted a view of Russia as in other respects superior to the western nations. Heavily influenced from the late eighteenth century by Romanticism and by the rise of nationalism in the west, they tended to depict European civilization as moribund. By this means they managed to define their own emergent nation in a contrastive way as having youth and promising futurity.